REFERENSI ENDOFORA DALAM CERPEN HARIAN RIAU POS - Rahmayanti, Santi; Hakim, Nursal; ', Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study titled is Endofora Reference in the Short Story of Riau Pos Daily. This study aimed to describe the reference endofora in Riau Pos daily short stories. The research is a qualitative research with descriptive methods. This research data is the entire sentence that uses a reference endofora, both based on the reference position and by type of object contained in Riau Pos daily short stories. Data obtained using the technique of reading. Then, the data were analyzed by identifying and classifying based on a reference shape endofora short story text. From the data obtained in the cliff Riau Pos daily, endofora reference forms are found among other personal references anaphora categories, demonstrative reference anaphora categories, comparative reference anaphora categories, personal references katafora categories, demonstrative reference katafora categories, and comparative references katafora categories. Types of personal pronouns used, among others, saya, aku, -ku, kami, kita, kamu, kau, -mu, ia, dia, beliau, -nya, and mereka. Kind of demonstrative pronouns used, among others, ini, itu, sana, and sini, while the comparative pronouns is used among others, sama, berbeda, and mirip.Keywords: endofora references, short story, Riau Pos daily, anaphora, katafora, personal references, demonstrative references, comparative references